2012
DOI: 10.4103/0976-500x.92515
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparative study of safety and efficacy of immediate release glucosamine HCL and glucosamine HCL sustained release formulation in the treatment of knee osteoarthritis: A proof of concept study

Abstract: Objectives:To compare the safety and efficacy of glucosamine HCl- sustained release (GLU-SR) with that of Glucosamine HCl- immediate release (GLU-IR) in patients with knee osteoarthritis (OA).Materials and Methods:This study involved 59 patients with knee OA, randomised to receive single oral dose of 1,500 mg, GLU-SR and GLU-IR for 60 days with 31 and 28 patients, respectively. The primary efficacy (pain and function) was assessed using visual analogue scale (VAS) and Western Ontario and McMaster Universities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In clinical trials, consumption of either glucosamine or chondroitin sulfate (CS) has been associated with a reduction in joint pain, improvement of joint function and reduction of joint space narrowing in patients with OA. 9 - 22 However, there is conflicting evidence as to the effectiveness of such treatments. 23 - 30 In vitro studies using glucosamine alone have found positive effects such as decreased interleukin-1 (IL-1) induced expression of matrix metalloproteinases, MMP-3 and MMP-13, cyclooxygenase-2 (COX-2), and nitric oxide synthase, reduced aggrecan degradation, and increased synthesis of aggrecan core protein 31 - 36 while others have found a decrease in prostaglandin E 2 (PGE 2 ) production induced by IL-1.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical trials, consumption of either glucosamine or chondroitin sulfate (CS) has been associated with a reduction in joint pain, improvement of joint function and reduction of joint space narrowing in patients with OA. 9 - 22 However, there is conflicting evidence as to the effectiveness of such treatments. 23 - 30 In vitro studies using glucosamine alone have found positive effects such as decreased interleukin-1 (IL-1) induced expression of matrix metalloproteinases, MMP-3 and MMP-13, cyclooxygenase-2 (COX-2), and nitric oxide synthase, reduced aggrecan degradation, and increased synthesis of aggrecan core protein 31 - 36 while others have found a decrease in prostaglandin E 2 (PGE 2 ) production induced by IL-1.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Nakamura et al showed that glucosamine significantly improved pain and swelling of arthritic joints compared with placebo in patients with rheumatoid arthritis (RA) . Matsuno et al , however, concluded that glucosamine was more effective for OA than RA , and Kulkarni et al reported that glucosamine HCl improved pain in 59 patients with knee OA . Recently, a randomized, double‐blind, placebo‐controlled trial by Sterzi et al showed that glucosamine HCl combined with chondroitin sulfate and bio‐curcumin was effective for knee OA .…”
Section: Introductionmentioning
confidence: 99%